2018
DOI: 10.1002/mc.22922
|View full text |Cite
|
Sign up to set email alerts
|

The histone deacetylase inhibitor LBH589 inhibits undifferentiated pleomorphic sarcoma growth via downregulation of FOS‐like antigen 1

Abstract: Undifferentiated pleomorphic sarcoma (UPS) is the second most frequent soft tissue sarcoma. Because of its resistance to chemotherapy, UPS patients are treated with surgical resection and complementary radiotherapy. However, since standard chemotherapy has not been established, unresectable or metastatic cases result in a poor prognosis. Therefore, the identification of a more effective therapy for UPS patients is needed. The development and progression of malignant tumors involve epigenetic alterations, and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 47 publications
(63 reference statements)
0
2
0
Order By: Relevance
“…These findings suggest that NTSR1 may be a potential diagnostic biomarker and treatment target for these cancers. In a previous study, we reported that FOS‐like antigen 1 (FOSL1), a transcriptional factor, was a therapeutic target of UPS cells . NTSR1 is a G‐protein‐coupled receptor that is the most intensively studied drug target, and it is targeted by many approved drugs .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings suggest that NTSR1 may be a potential diagnostic biomarker and treatment target for these cancers. In a previous study, we reported that FOS‐like antigen 1 (FOSL1), a transcriptional factor, was a therapeutic target of UPS cells . NTSR1 is a G‐protein‐coupled receptor that is the most intensively studied drug target, and it is targeted by many approved drugs .…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, we reported that FOS-like antigen 1 (FOSL1), a transcriptional factor, was a therapeutic target of UPS cells. 41 NTSR1 is a G-protein-coupled receptor that is the most intensively studied drug target, and it is targeted by many approved drugs. 8 In this regard, NTSR1 is more likely to be a therapeutic target than FOSL1.…”
Section: Discussionmentioning
confidence: 99%